2017
DOI: 10.2196/jmir.7854
|View full text |Cite
|
Sign up to set email alerts
|

Internet Hospitals in China: Cross-Sectional Survey

Abstract: BackgroundThe Internet hospital, an innovative approach to providing health care, is rapidly developing in China because it has the potential to provide widely accessible outpatient service delivery via Internet technologies. To date, China’s Internet hospitals have not been systematically investigated.ObjectiveThe aim of this study was to describe the characteristics of China’s Internet hospitals, and to assess their health service capacity.MethodsWe searched Baidu, the popular Chinese search engine, to ident… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
78
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(81 citation statements)
references
References 8 publications
0
78
2
1
Order By: Relevance
“…Despite these limitations, the current study reports the first national survey on eHealth behaviors in China and one of the first from middle- and low-income countries. The low adoption rates of eHealth behaviors and significant digital divide suggested that the general Chinese population might not yet be ready for the “Internet hospitals” or “intelligent healthcare” ( 4 , 5 ). Literature from high-income countries suggested that the ubiquitous Internet access has created a persistent digital divide and the eHealth movement has exacerbated health disparities ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite these limitations, the current study reports the first national survey on eHealth behaviors in China and one of the first from middle- and low-income countries. The low adoption rates of eHealth behaviors and significant digital divide suggested that the general Chinese population might not yet be ready for the “Internet hospitals” or “intelligent healthcare” ( 4 , 5 ). Literature from high-income countries suggested that the ubiquitous Internet access has created a persistent digital divide and the eHealth movement has exacerbated health disparities ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Chinese government is encouraging all healthcare agencies to utilize China's robust telecommunication infrastructure to assist in national healthcare reform initiatives; an increasing number of government-sponsored Internet hospitals and eHealth interventions have been established ( 4 6 ). However, a closer look at the data from the burgeoning eHealth initiatives revealed that most eHealth interventions were pilot projects conducted in major metropolitans; ( 5 , 6 ) and the surveys on attitudes toward eHealth programs were typically collected from medical professionals or based on small convenience samples ( 7 , 8 ). Data are missing on the readiness of eHealth adoption in the general Chinese population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is significant support and momentum for the implementation of eHealth based selfmanagement interventions in China. China had 731 million internet users (penetration rate 53%) and 1.3 billion mobile phone users (penetration rate of 90%) in 2016, and this number is still growing [23][24][25][26]. Furthermore, policymakers and care experts in China have recently launched the national health strategy 'Healthy China 2030'.…”
Section: Opportunities For Ehealth Interventions In Chinamentioning
confidence: 99%
“…In China, Internet hospitals provide innovative health care directly through Internet technologies such as websites and mobile apps. In a study of the 43 established Internet hospitals, 18 (42%) of the hospitals provide access to outpatient health care via mobile app [ 13 ]. Related studies have focused on the contributions from the use of mHealth apps to specific disease outcomes [ 14 - 16 ].…”
Section: Introductionmentioning
confidence: 99%